Hubungan Albuminuria dan Laju Filtrasi Glomerulus pada Pasien Diabetes Melitus Tipe 2 yang Tidak Terkontrol - Parinding, Vinny Vania; Ilmiawan, Muhammad In'am; Fitrianingrum, Iit; Trianto, Heru Fajar; Mardhia, Mardhia (Faculty of Medicine, Universitas Andalas, 2022)
Diabetes mellitus is a chronic metabolic disorder characterized by hyperglycemia. Patients with diabetes mellitus require optimal glycemic control. Poorly controlled diabetes mellitus is at risk for complications, such as diabetic nephropathy. Diabetic nephropathy is characterized by albuminuria and can lead to decreased Glomerular Filtration Rate (GFR). Objectives: To determined the relationship between albuminuria and GFR in a patient with poorly controlled type 2 diabetes mellitus. Methods: This research was conducted at the Pontianak Branch of Prodia Health Clinic Laboratory in March 2021, using secondary data of laboratory examination results from DM patients in the 2020 period. This research was observational analytics with a cross-sectional approach. The number of samples that comply with the research criteria was 273 people. Bivariate analysis using Spearmanâ€™s correlation test. Results: Spearman's correlation test results showed significance (p=0.001) and correlation coefficient (r=0.209). Conclusion: Albuminuria and GFR in a patient with poorly controlled type 2 diabetes mellitus are significantly and positively correlated.Keywords: Â albuminuria, poorly controlled type 2 diabetes mellitus, glomerular filtration rate